ANALISIS IMPLEMENTASI MEDIA PEMBELAJARAN DALAM MENDUKUNG PROSES PEMBELAJARAN DI KELAS IV SDN 7 METRO PUSAT - Rahayu Sekarningrum, Dwi; Widya Utami, Astri; Puspita, Dea; Aulia, Marsya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning media serve as an essential component in supporting effective learning processes in elementary schools. However, their implementation is influenced by several factors, including teachers' planning, school support, the availability of learning facilities, and students' characteristics. This study aimed to analyze the implementation of learning media in supporting the learning process in the fourth grade of SD Negeri 7 Metro Pusat. This study employed a descriptive qualitative approach. The participants consisted of the school principal, one fourth-grade teacher, and four fourth-grade students who were purposively selected as the research participants. Data were gathered through semi-structured interviews and documentation and analyzed through data reduction, data display, and conclusion drawing. The results showed that the use of learning media had been planned during the preparation of teaching modules and adjusted to the learning objectives and characteristics of the subject matter. Teachers integrated both concrete and digital media into classroom instruction, while the school supported their implementation through the provision of learning facilities, teacher training, and academic supervision. The main challenges included the limited availability of digital learning media and differences in students' participation during classroom activities. Effective implementation of learning media requires teacher readiness, school support, and the appropriate use of learning media based on instructional needs.